ANALISIS NILAI KARAKTER PADA LAGU ANAK : APAKAH LAGU ANAK DAPAT DIIMPLEMENTASIKAN PADA PEMBELAJARAN TEMATIK - Wening Sari; Felinda Nurmalitasari; Armelia Rahmi Lubis; Noormalita Dian Puspita; Ali Mustadi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to provide a general description of children song lyrics analysis and to describe the implementation of children songs in thematic learning at grades I - III of elementary school. This was a content analysis study that utilized qualitative approach. The data analysis technique consisted of: 1) collecting data; 2) selecting samples; 3) recording; 4) reducing; 5) making conclusions; and 6) narrating. The results of this study revealed that: 1) children songs had the benefit of conveying messages in a fun way; 2) in this analysis, one song out of eight songs contained the character values that did not match the 18 characters taught to students; 3) there were a lot of good character values in children songs, for example religious, honest, responsibility, discipline, independent, care for the environment, work hard, and care for others. Those character must be instilled for elementary school students, especially for students of grade I to III; 4) children songs could be implemented in thematic learning either to start the learning, as a learning material or as an example in giving assignments to students.